REKONSTRUKSI PENDIDIKAN ISLAM PADA MASA KERAJAAN TURKI UTSMNAI, SAFAWI, DAN MUGHAL PADA PENDIDIKAN ISLAM MASA KINI - Ramadani, Kurnia Rahma; Zaman, Badrus (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
In medieval times there were three major empires, namely the Ottoman Turkish, Safavid and Mughal Empires. The three kingdoms had their own focus and strategies in the field of education that are interesting to be reconstructed to be applied in the current era. This research uses the library research method. The important result of this research is the modernization of Islamic education as a result of the reconstruction of education during the three empires that can be applied to education in the present era. Modernization of Islamic education is important to do because it is considered as the right step in balancing Islamic education with the progress of the current era. Modernization of Islamic education needs to be done in order to provide changes in thinking in the field of Islamic education, improve the old education system into a new system in order to improve the quality of Islamic education. In Indonesia, judging from the history of Islamic education during the three great kingdoms, modernization of Islamic education can be done in several aspects, such as educational institutions, learning methods, curriculum, and graduate orientation.With the modernization of Islamic education, it is expected to produce graduates who have competence in the fields of religion and general science.